Transverse Myelitis Associated with Cryptococcus neoformans in an Immunocompetent Patient - David B. Villafuerte; Marco F. Passeri; Rayan Qazi; Moulika Baireddy; Fernando L. Sanchez (Case Reports in Infectious Diseases)
Cryptococcus neoformans is a microscopic fungus that despite its pervasiveness in the environment rarely causes infection in immunocompetent patients. In immunosuppressed patients, infections involving the central nervous system (CNS) usually present as meningitis or meningoencephalitis. Cryptococcal infections are known to cause significant morbidity and mortality in immunosuppressed patients as it is difficult to eradicate even with adequate antifungal treatment. A 44-year-old Hispanic male presented to the hospital with headache, progressive urinary retention, neck and back pain, and right upper and bilateral lower extremity weakness for five days. Imaging revealed small foci in the white matter and revealed diffuse abnormal signal involving the cervical medullary junction extending up to the thoracic spine. Analysis of cerebral spinal fluid (CSF) obtained via lumbar puncture was positive for the Streptococcus antigen with cultures also growing Cryptococcus neoformans. Upon evaluation, patient was not found to be immunocompromised. This report works to highlight an atypical presentation of a cryptococcal CNS infection to raise awareness amongst clinicians hoping to prevent a delay in diagnosis of this disease given its high mortality.